Milho, amido ou caroço de algodão associados à glicerina bruta em dietas para ovinos - Perez, Henrique Leal [UNESP] (2015)
The objective of this work was to evaluate the effects of the combination of crude glycerin, waste from the production of biodiesel, with the cottonseed, corn or starch on the carcass characteristics, meat, performance, ruminal parameters and production of methane gas and carbon dioxide. Were used 39 lambs contemporaries not castrated, with approximately 70 days of age and average body weight of 19 kg. The proportion roughage concentrated was 30:70. The statistical design was completely randomized with three diets and 13 replicates. There was no effect (P> 0.05) for average daily gain, with an average 0.160 kg / day, days of feedlot with an average of 101.26 days and feed conversion to 5.65. For dry matter intake effect was observed (P <0.05) reductive for diet with cottonseed. For nutrient intake effect was observed (P <0.05) for the variable intake of crude protein, acid detergent fiber and extract ethereal not having effect (P>0.05) on intake only for neutral detergent fiber. There was a significant (P<0.05) reductive digestibility of dry matter and ether extract digestibility for treatment CA and greatest digestibility for acid detergent fiber (P<0.05). Crude protein and neutral detergent fiber had no effect (P> 0.05). For the determination of ammonia nitrogen and pH, the design was used in Latin Square, triple 3x3 using nine cannulated animals in the rumen. Methane production was evaluated per in vitro incubation of the diets for 24 hours at 39°C. There was no effect (P> 0.05) to pH values of rumen fluid, with averages of 6.22; 6.26 and 6.31 for diets A, CA and M respectively. For N-NH3 concentrations were observed greatest values on the first two hours after feeding. For the production of methane gas (CH4) and carbon dioxide (CO2), there was difference (P<0.05) for the production expressed as total volume of gas, the CA diet has resulted in the lowest value. For the production of CH4 and CO2 on mL/g dry matter (DM) incubated ...